2002
DOI: 10.1007/s00467-002-0889-z
|View full text |Cite
|
Sign up to set email alerts
|

Renal tract ultrasonography and calcium homeostasis in Williams-Beuren syndrome

Abstract: Renal ultrasound scan, circulating creatinine and calcium, and the urinary calcium excretion rate were investigated in 57 patients with clinically and genetically typical Williams-Beuren syndrome (25 female and 32 male subjects, aged from 1.0 year to 23 years, median 8.5 years) on regular follow up at our institution. Twenty-three unilateral abnormalities were detected in 20 patients: pelvic dilatation ( n=6), renal hypoplasia ( n=5), isolated renal cyst ( n=3), kidney surface irregularity ( n=3), kidney dupli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 13 publications
2
21
0
2
Order By: Relevance
“…Eleven of 45 (24%) experienced urinary tract structural abnormalities at abdominal ultrasound examination. This percentage is consistent with previously reported studies [Pankau et al, 1996;Sforzini et al, 2002].…”
Section: Discussionsupporting
confidence: 94%
“…Eleven of 45 (24%) experienced urinary tract structural abnormalities at abdominal ultrasound examination. This percentage is consistent with previously reported studies [Pankau et al, 1996;Sforzini et al, 2002].…”
Section: Discussionsupporting
confidence: 94%
“…35 The authors concluded that, in WS, hypercalcemia is not frequent and hypercalciuria is rare after the first 1 year of life; they speculated that the issue of disturbed calcium homeostasis in WS has been overemphasized in the past. Our report challenges these views, given the severity of hypercalcemia for patients 1 and 2, nephrocalcinosis for patients 2 and 3, and the age of onset and recurrence of hypercalcemia for patient 3.…”
Section: Discussionmentioning
confidence: 98%
“…The moderate–severe forms most often occur within the first year of life and resolve by age 4 12 13. Nephrocalcinosis is detected in approximately 5%–10% of patients undergoing renal ultrasonography 8. Hypercalcaemia causes dehydration by directly affecting renal distal tubular function, impairing concentrating ability leading to polyuria.…”
Section: Discussionmentioning
confidence: 99%